Integrasi Epistemologi Islam dalam Pengembangan Kebijakan Pendidikan Kontemporer - Asih, Dianing Banyu; Nugraha, Mulyawan Safwandy (Peneliti.net, 2025)
Contemporary education policy is faced with the challenges of globalization, technological advances, and the need for inclusiveness, so a new approach is needed that is able to respond to these changes critically and adaptively. This research aims to analyze the integration of Islamic epistemology, which emphasizes spiritual and moral values, in the design of more inclusive and educational policies. The main focus is the integration of Islamic epistemology, which emphasizes spiritual and moral values, as the basis for a more inclusive and sustainable education policy. However, previous research has not examined the comprehensive application of Islamic epistemology in contemporary education policy. The method used is a literature study with a qualitative approach to identify the relevance of Islamic epistemology in the educational context. The results show that the integration of Maqashid Sharia principles can create more equitable education policies, address access inequality, and provide solutions for social, economic, and environmental sustainability. The use of Islamic financial instruments such as zakat and waqf can also expand access to education for marginalized groups, increasing inclusivity in real terms. The implications of this research provide practical guidance for the development of education policies based on Islamic values that are holistic and oriented towards long-term welfare.